Climate change in healthcare: Exploring the potential role of inhaler prescribing - Joachim Starup‐Hansen; Henry Dunne; Jonathan Sadler; Anna Jones; Michael Okorie (Wiley, 2020)
Abstract Climate change has been described as the biggest global health threat of the 21st century. As a result, governments around the world are committing to legislative change in order to reduce greenhouse gas emissions (GHGEs). The healthcare sector makes a significant contribution to GHGEs and in line with national legislation in the UK, the NHS has recently committed to achieving net zero emissions by 2050. The management of asthma and COPD largely depends on the prescribing of medications that are delivered through inhalers. In the UK, the use of pressurized metered dose inhalers (pMDIs), which rely on hydrofluorocarbon (HFC) propellants accounts for 3.5% of the NHS's total carbon footprint. In contrast, dry powder inhalers (DPIs) have a much lower carbon footprint due to the absence of a HFC propellant. Here we review evidence of the impact of inhaler choices across four domains: environmental impact, clinical effectiveness, cost effectiveness and patient preferences. We find that as well as a lower global‐warming potential, DPIs have additional benefits over pMDIs in other domains and should be considered first line where clinically appropriate.